Multiple Autoimmune Syndrome Type III. Case Report (Revista de Medicina Clinica, 2022)
We present the case of a female patient with a history of type 1 diabetes mellitus who started with dysphagia, accompanied by dryness in the oral and vaginal cavity. After a thyroid scan and salivary gland biopsy, the diagnosis of Hashimoto's thyroiditis and associated Sjögren's syndrome was confirmed.
Keywords: Autoimmune thyroid disease; Sjögren's syndrome; Type 1 diabetes